ANALISIS PENGARUH CORPORATE GOVERNANCE, DAN OWNERSHIP STRUCTURE TERHADAP CAPITAL STRUCTURE DENGAN FIRM SIZE SEBAGAI VARIABEL KONTROL (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Surya Maulana Ibrahim; Irene Rini Demi Pangestuti (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of Corporate Governance and Ownership Structure on DAR in manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2020 period. This study uses DAR as the dependent variable. The independent variables used are Board size (BOD), Independent Commissioner (IC), Audit Committee (AC), Managerial Ownership (MO), Institutional Ownership (IO) with Firm Size as a control variable. This study uses secondary data obtained from the annual reports of Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) during the 2016-2020 period. The number of samples used was 33 with purposive sampling method, so that a total of 165 observations were obtained. This research uses multiple linear regression method with IBM SPSS 26 program which consists of classical assumption test, f statistic test, t statistic test, and coefficient of determination (R2) test. During the observation period, it shows that the data in this study are normally distributed. This shows that the data used have met the requirements to use the multiple linear regression equation model. The results of this study indicate that Board Size and Independent Commissioner have a significant negative effect on DAR, Managerial Ownership and Institutional Ownership have a significant positive effect on DAR. Meanwhile, the Audit Committee has no effect on DAR.